Implementation of Ecosystem Approach to Aquaculture (EAA) on Tilapia Commodities in Klaten District - Nugroho, Adi; Priyono, Susilo Budi; Suadi, Suadi (Universitas Gadjah Mada, 2024)
Ministry of maritime affairs and fisheries (MMAF) has issued guidance on ecosystem approach aquaculture (EAA) as a tool for profitable and sustainable management of aquaculture areas. The Minapolitan area of Klaten district with the superior commodity Tilapia fish has not yet fully implemented EAA. The purpose of this study are: (1) evaluating the management of tilapia fish commodity cultivation areas in Klaten district based on EAA indicators and (2) providing recommendations for interventions to improve the management of tilapia cultivation fishery areas in Klaten district based on EAA indicators. The methods of data analysis used in this study is quantitative analysis using descriptive approach. Data collection uses triangulation techniques where respondents are determined intentionally (purposefully). The study site was in Minapolitan Area 1 (Karanganom, Tulung and Polanharjo) and Minapolitan Area 2 (Ngawen, Kebonarum, and South Klaten) of Klaten regency. The result showed that the management of aquaculture areas with Tilapia as a commodity in Klaten district based on the EAA parameter is in adequate condition with a value of 2.26 for Minapolitan Area 1 and 2.13 for Minapolitan Area 2. Recommendations for interventions are improvements to institutional parameters, monitoring, and evaluation, as well as the role of environmental management in the area.